2009
DOI: 10.1080/15226510902787302
|View full text |Cite
|
Sign up to set email alerts
|

VETIVER GRASS,VETIVERIA ZIZANIOIDES: A CHOICE PLANT FOR PHYTOREMEDIATION OF HEAVY METALS AND ORGANIC WASTES

Abstract: Glasshouse and field studies showed that Vetiver grass can produce high biomass (>100t/ tha(-1) year(-1)) and highly tolerate extreme climatic variation such as prolonged drought, flood, submergence and temperatures (-15 degrees - 55 degrees C), soils high in acidity and alkalinity (pH 3.3-9.5), high levels of Al (85% saturation percentage), Mn (578 mg kg(-1)), soil salinity (ECse 47.5 dS m(-1)), sodicity (ESP 48%), anda wide range of heavy metals (As, Cd, Cr, Cu, Hg, Ni, Pb, Se, and Zn). Vetiver can accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(122 citation statements)
references
References 69 publications
5
108
0
9
Order By: Relevance
“…Due to the expensive nature of the conventional remediation methods for heavy metal contamination [9], phytoremediation technologies are continuously being researched for possible solutions. The level of heavy and toxic metals (Pb, Cr, Hg, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Due to the expensive nature of the conventional remediation methods for heavy metal contamination [9], phytoremediation technologies are continuously being researched for possible solutions. The level of heavy and toxic metals (Pb, Cr, Hg, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the plant might not have been able to uptake other metals, resulting in negligible reduction in concentration of these metals in the leachates. In a phytoremediation study, Danh et al (2009) mentioned that Cd is accumulated in the shoots of Vetiver plant while Pb is accumulated both in shoots as well as roots. Hooda (2007) also reported that rhizospheric bacteria facilitate the uptake of heavy metals by phytoextraction/phytosequestration mechanism.…”
Section: Heavy Metal Analysismentioning
confidence: 99%
“…The tank bottom oil sludge used for the experiment was collected from Gujarat oil refinery, Vadodara, India. The plant used for the study was Vetiveria zizanioides due to its properties such as dense and massive root system, high biomass production, rapid growth rate, high tolerance and adaptability to a wide range of climatic and environmental conditions, ability to accumulate heavy metals and tolerance to petroleum hydrocarbon toxicity (Danh et al 2009). V. zizanioides saplings (15 days old) of same the height (30 cm) were purchased from Shri Shell nursery, Nagpur.…”
Section: Site Preparation and Experimental Set Upmentioning
confidence: 99%
“…Another unique characteristic of VG is that it has high tolerance to elevated concentrations of heavy metals such as As, Cd, Cu, Cr, Pb, Hg, Ni, Se and Zn in the soil [1,11,12]. Besides, VG has high tolerance and adaptability to extreme edaphic conditions such as soil with high acidity and alkalinity.…”
Section: Introductionmentioning
confidence: 99%
“…Vetiver grass (VG) is a tall (1-2 m), fast-growing, perennial tussock grass. It has a long (3-4 m), massive and complex root system, which can penetrate to the deeper layers of the soil [1][2][3][4]. The dense high fiber, fine root system that forms an enormous volume accelerates habitat for many symbiotic bacteria, and fungi made the ecology system naturally contributes to the pollutant uptake.…”
Section: Introductionmentioning
confidence: 99%